Highly Selective Fluorescent Probe With an Ideal pH Profile for the Rapid and Unambiguous Determination of Subcellular Labile Iron (III) Pools in Human Cells. (2nd June 2022) - Alhawsah, Bayan; Yan, Bing; Aydin, Ziya; Niu, Xiangyu; Guo, Maolin
Abstract: A convenient tool for detecting iron ions in subcellular structures is desired for better understanding its roles in biological systems. In this work, a new Fe 3+ sensor, 2-(2-((1-(6-acetylpyridin-2-yl)ethylidene)amino)ethyl)-3', 6'-bis(diethylamino)spiro[isoindoline-1, 9'-xanthen]-3-one (RhPK), which operates across the entire cellular pH range and is capable of unambiguously detecting Fe 3+ ion in live human cells at subcellular resolution, is reported. The sensor exhibits high selectivity and sensitivity toward Fe 3+ with a rapid fluorescence response and a 12-fold increase in intensity upon the addition of 1 equivalent Fe 3+ at pH 7.3. RhPK forms a 1:1 complex with Fe 3+ with an apparent binding constant 1.54 × 10 7 M −1 and a detection limit of 50 nM. The sensor is stable between pH 4.2 and 9.0 and operates across the whole cellular pH range. Cell imaging demonstrates the ability of the sensor to unambiguously detect basal level Fe 3+ as well as its dynamic changes in real-time in live cells at subcellular resolution, with one labile Fe 3+ pool identified in mitochondria in human primary fibroblast (ws1) cells for the first time and two Fe 3 + pools confirmed in mitochondria and endo/lysosomes in human SH-SY5Y neuroblastoma cells, suggesting different cell types have distinctive Fe 3+ storage in subcellular compartments. The RhPK probe is powerful for rapid and sensitive bioimaging of Fe 3+ at subcellular level, enabling the unambiguous detection of labile Fe 3+ pools at the entire cellular pH range, which is of great significance to understand the biological chemistry of Fe 3+ and its roles in physiological processes and diseases.